WORK: DIMENSIONS, MEANINGS AND EXTENSION OF THE CONCEPT - Viviane Nascimento Silva; Gilmar Ribeiro dos Santos; Sarah Jane Alves Durães (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This article aims at the realization of theoretical reflections about the meaning and function of work in society. A visit to the classics, especially Emile Durkheim and Karl Marx, allows us to problematize the connotations of work, passing through a historical trajectory of the work until pointing out some of the contradictions of the capitalist mode of production. In elucidating aspects of productive restructuring, there are possibilities for debate about the process of deconstruction and expansion of the concept of work itself. The need to reflect on the work is fundamental to understand the modifications and contradictions assumed as a theoretical category and practical experience in the course of the history of humanity. If the analysis follows from the principles of society's production and reproduction systems, it will certainly be possible to perceive more clearly the motives which led to the recurring changes in the world of work. The conditions necessary to carry on the work or demanded from its realization also change according to the economic, historical, political, social and cultural context in which men live in society.